PENGARUH MODEL CIRCUIT LEARNING TERHADAP KEMAMPUAN MENULIS TEKS NARASI BERBANTUAN MEDIA MIND MAPPING PADA SISWA KELAS IV MADRASAH IBTIDAIYAH DARUL FALAH SELAKAU - Gita Febrianti; Zulfahita; Evinna Cinda Hendriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to: 1) determine differences in students' narrative writing abilities. 2) to find out how big the influence of the circuit learning model assisted by mind mapping media is. The type of research design used is a Pre-Experimental design, namely One Group Pre-test Posttest design. The population in this study was all class IV students of Madrasah Ibtidaiyah Darul Fallah Selakau, consisting of 30 class A students and 30 class B students, so a total of 60 people. The sample in this research is a population that is part of the number and characteristics of that population.